Watch me (this is my truth). - De Ridder, An; De Schampheleire, Piet; De Schampheleire, Sofie; Delanghe, Babet; Huet, Nan; Saey, Peggy; Soetaert, Ronald; Van Eeckhaut, Marijke; Van Hecke, Piet (Antwerpen : MUHKA (Museum van Hedendaagse Kunst Antwerpen), 2000)
van Oost, Jan ; Bleus, Guy ; Visch, Henk ; Vertessen, Liliane ; Muñoz, Juan ; Dumas, Marlene ; Cole, Willem ; Abramovic, Marina & Ulay ; Blacker, Kate ; van Bergen, Thé ; Copers, Leo ; Dujourie, Lili ; De Bruyckere, Berlinde ; Pistoletto, Michelangelo
Nederlands
Watch me (this is my truth), MUHKA (Museum van Hedendaagse Kunst Antwerpen) Antwerpen, 21 mei - 31 augustus 2000
boek